IMPROVEMENT PROPOSALS IN CONTRACT MANAGEMENT AT THE FEDERAL UNIVERSITY OF SAO CARLOS THROUGH PROCESS MANAGEMENT - Ture, Vanessa Stevan [UNESP] (Escola Nacl Adm Publica-enap, 2022)
The aim of this work is to contribute to the improvement of the management and inspection of outsourced service contracts at the Sao Carlos campus of the Federal University of Sao Carlos through process management. From a methodological point of view, the study is classified as exploratory research, with a qualitative approach to the problem and characterized as a case study. In order to achieve the proposed objective, a mapping and analysis of the current situation of the hiring process of outsourced workers at the university was carried out, based on the current legislation that provides guidance on this type of hiring. As a complement to the data collection, it was carried out a structured interview with contract inspectors. Thus, sixteen proposals for possible improvements were generated, suggesting the application of management tools for processes, that can result in the construction of future situations, in the standardization of inspection instruments, planning suggestions and models of procedures for contract management.
Keywords: contract management; contractual inspection; outsourcing; process management